Sonogashira Reaction of Aryl and Heteroaryl Halides with Terminal Alkynes Catalyzed by a Highly Efficient and Recyclable Nanosized MCM-41 Anchored Palladium Bipyridyl Complex - Lin, Bo-Nan (Molecules, 2010)
A heterogeneous catalyst, nanosized MCM-41-Pd, was used to catalyze the Sonogashira coupling of aryl and heteroaryl halides with terminal alkynes in the presence of CuI and triphenylphosphine. The coupling products were obtained in high yields using low Pd loadings to 0.01 mol%, and the nanosized MCM-41-Pd catalyst was recovered by centrifugation of the reaction solution and re-used in further runs without significant loss of reactivity.